1999
DOI: 10.1073/pnas.96.3.1019
|View full text |Cite
|
Sign up to set email alerts
|

CD48-deficient mice have a pronounced defect in CD4+T cell activation

Abstract: We have generated mice deficient in the expression of the lymphocyte cell surface antigen CD48 (Blast-1, BCM1, sgp-60) by gene targeting in embryonic stem cells. Mice homozygous for the CD48 mutation (CD48 ؊͞؊ mice) are severely impaired in CD4 ؉ T cell activation. Proliferative responses to mitogens, anti-CD3 mAb, and alloantigen are all reduced. Experiments in which T cells and antigen-presenting cells from either wild-type or CD48 ؊͞؊ mice were cocultured reveal that CD48 is important on both T cells and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 31 publications
4
71
0
Order By: Relevance
“…These results confirmed that CD48 can activate cells using 2B4 as ligand. This is consistent with the reported role of CD48 in potentiating T cell responses (41). Thus, we see that this system can be used to study receptors that can both increase (activate) and decrease (inhibit) TCR-mediated IL-2 secretion.…”
Section: B6 Alleles Of 2b4 and Cd48 Can Modulate Tcr Activitysupporting
confidence: 75%
“…These results confirmed that CD48 can activate cells using 2B4 as ligand. This is consistent with the reported role of CD48 in potentiating T cell responses (41). Thus, we see that this system can be used to study receptors that can both increase (activate) and decrease (inhibit) TCR-mediated IL-2 secretion.…”
Section: B6 Alleles Of 2b4 and Cd48 Can Modulate Tcr Activitysupporting
confidence: 75%
“…Interestingly, CD2 Ϫ/Ϫ mice have a similar phenotype to wt mice, whereas T cells from CD48 Ϫ/Ϫ mice have a severe reduction in proliferation and IL-2 production in response to lectins, anti-CD3 Ab, and alloantigens (30,(35)(36)(37). Possibly, 2B4 compensates for the lack of CD2 in CD2 Ϫ/Ϫ mice, which may explain why the phenotype of CD2 Ϫ/Ϫ mice is less pronounced.…”
Section: Discussionmentioning
confidence: 97%
“…The significance of this finding with regard to T cell function or the gender-specific rejection of B16 cells remains to be seen. CD48-deficient mice demonstrated a developmental defect in the thymus and a profound defect in the activation of CD4 T cells through the TCR (36). Before CD48 was identified as the ligand for 2B4, CD2 was recognized as the CD48 ligand.…”
Section: Discussionmentioning
confidence: 99%